2022
DOI: 10.3393/ac.2020.09.02
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes with implementation of an Enhanced Recovery After Surgery pathway for patients undergoing elective colorectal surgery in the Philippines

Abstract: Objectives: This study aims to evaluate surgical outcomes (i.e. length of stay (LOS), 30-day morbidity, mortality, reoperation, and readmission rates) with the use of the ERAS pathway, and determine its association with the rate of compliance to the different ERAS components. Methodology: This was a prospective cohort of patients, who underwent the following elective procedures: stoma reversal (SR), colon resection (CR), and rectal resection (RR). The primary endpoint was to determine the association of compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…This trend has also been demonstrated in the NZ context, where patients undergoing elective colorectal surgery managed within an ERAS pathway had shorter hospital stays without increased morbidity or mortality 24 . However, post‐operative LOS at our institution was longer than contemporary LOS figures quoted by recent studies which range from 3 to 5 days 7,25–29 . This finding could reflect the rurality of our hospital; patients living up to 4 h away from the hospital, and our poor compliance in some of the ERAS protocol components.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This trend has also been demonstrated in the NZ context, where patients undergoing elective colorectal surgery managed within an ERAS pathway had shorter hospital stays without increased morbidity or mortality 24 . However, post‐operative LOS at our institution was longer than contemporary LOS figures quoted by recent studies which range from 3 to 5 days 7,25–29 . This finding could reflect the rurality of our hospital; patients living up to 4 h away from the hospital, and our poor compliance in some of the ERAS protocol components.…”
Section: Discussionsupporting
confidence: 68%
“…24 However, post-operative LOS at our institution was longer than contemporary LOS figures quoted by recent studies which range from 3 to 5 days. 7,[25][26][27][28][29] This finding could reflect the rurality of our hospital; patients living up to 4 h away from the hospital, and our poor compliance in some of the ERAS protocol components.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the length of postoperative hospital stay and early postoperative mortality rates did not differ between the two periods [35]. The enhanced recovery program, already adopted by many societies for colorectal cancer management, has been proven to be suitable even for fragile patients [41][42][43]. This could be one of the reasons why most studies did not show a difference in the length of hospital stay.…”
Section: Surgical Complications After Colorectal Cancer Surgery Durin...mentioning
confidence: 95%
“…Recently, enhanced recovery after surgery (ERAS) program has shown that early rehab and early feeding in postoperative patients are good prognostic factors for patients' recovery [ 110 111 112 113 114 115 ]. The ERAS program recommends catheter removal on postoperative day 1, but surgeons should be taken care when removing it due to the risk of nerve damage during rectal cancer surgery.…”
Section: How To Improve Surgical Outcomesmentioning
confidence: 99%